OPTIMASI FORMULASI FAST DISINTEGRATING TABLET (FDT) DIFENHIDRAMIN HCL DENGAN AC-DI-SOL SEBAGAI SUPERDISINTEGRANT DAN MANITOL SEBAGAI BAHAN PENGISI - Raihanah Raihanah; Noval Noval; Agustina Hotma Uli Tumanggor (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Diphenhydramine HCl is a drug that is used to reduce and block the effects of histamine in the body, to speed up the action of the drug and increase its effect, especially for pediatric and elderly patients. FDT is made with the active ingredient Diphenhydramine HCl combined with superdisintegrant Ac-Di-Sol and Mannitol as filler. To determine the effect of the optimal combination of Ac-Di-Sol and Mannitol in the FDT Diphenhydramine HCl formulation. This study uses a Quasi Experiment Design method with a Non Equivalent Control Group design. FDT was made with 5 different Ac-Di-sol and Mannitol formulations by direct compression method and then evaluated for moisture content, flow rate, angle of repose, compressibility, uniformity of size, uniformity of weight, friability, hardness, disintegration time, disintegration time and wetting time. The results of the research are descriptive analysis and Simplex Lattice Design using Software Design Expert Version 10.0. Evaluation of the physical properties of the powders showed that all formulations met the requirements of moisture content, angle of repose and compressibility, while the flow properties of all formulations did not meet the requirements. The results of the evaluation of the physical properties of FDT produced a clean white color, odorless, with a slightly bitter taste. All FDT formulations met the requirements for uniformity of weight, friability, hardness, disintegration time, and disintegration time, while the results of the uniformity of size and wetting time of all formulations did not meet the requirements. The combination of the concentration ratio of Ac-Di-Sol and Mannitol affects the aspects of brittleness, hardness, disintegration time and wetting time. Formulation 4 is the optimal formulation with the composition of Ac-Di-Sol 12.5 mg and Mannitol 7.5 mg with a desirability value of 0.953.